Patriotic information systems - Loendorf, Todd.; Garson, G. David; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book discusses how, with its non-participatory enforcement ethos, its inherent bias against freedom of information, and its massive claims on IT budget resources, the information technology security system of the future may be even less hospitable to the democratic visions which some theorists once anticipated would be among the most important contributions of information technology to society"--Provided by publisher.
Section IV. Conclusion -- About the contributors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 13, 2010).
Keywords: Computer security -- Law and legislation -- United States; Data protection -- Law and legislation -- United States; Information technology -- Security measures -- United States; Electronic surveillance -- United States; Public records -- Access control -- United States; Freedom of information -- United States; Privacy, Right of -- United States; Electronic books